Multiscale Resource Selection by Woodland Caribou in Saskatchewan's Boreal Shield: A Fundamental Step Towards Managing a Threatened Species - Stewart, Kathrine Mary 1985- (2016)
Resource selection is a dynamic behavioural process by which individuals choose resource units (e.g., pixels or points on a landscape) disproportionate to their availability in order to maximize fitness. Because it influences how individuals, and thus populations, are distributed through space and time, understanding how animals choose resource units is fundamental to developing effective, long-term resource management and species’ conservation strategies. One of the first steps in assessing conservation prospects for a species is identifying critical habitat, which is habitat necessary for a species to carry out all of its life functions (e.g., breeding, foraging, migrating etc.). Resource selection functions (RSFs), which are functions proportional to the probability of use of a resource unit, provide a means to both quantify animal-environment interactions and predict species’ probability of occurrence on a given landscape. When linked to information concerning a species survival and reproduction (e.g., birth, death and recruitment rates), RSFs can be used to determine which resource units constitute critical habitat for a species. I used RSFs to model seasonal resource selection at two spatial scales by a population of woodland caribou (Rangifer tarandus caribou) in Saskatchewan’s Boreal Shield. Across much of Canada, woodland caribou populations are declining due to anthropogenic-driven habitat loss, fragmentation and alteration; as a result, they are listed as ‘Threatened’ on Canada’s Species at Risk Act. However, compared to other caribou populations in Canada, caribou in Saskatchewan’s Boreal Shield are exposed to unusually low levels of human activity (est. 3% landscape disturbed by humans) but relatively high levels of natural forest fires (est. 55% of landscape burned in the past 40 years). My thesis offers valuable, benchmark insight into how caribou use resources relative to their availability under this largely natural disturbance regime, which likely reflects the pristine conditions under which ...